1999
DOI: 10.1038/sj.onc.1202663
|View full text |Cite
|
Sign up to set email alerts
|

Methylation and silencing of the Thrombospondin-1 promoter in human cancer

Abstract: Neovascularization is a common feature of many human cancers, but relatively few molecular defects have been demonstrated in genes regulating angiogenesis. Decreased expression of Thrombospondin-1 (THBS1), a P53 and Rb regulated angiogenesis inhibitor, has been observed in some human tumors, including glioblastoma multiforme (GBM). To study whether methylationassociated inactivation is involved in down-regulating THBS1 expression in cancer, we analysed the methylation status of THBS1 in several cell lines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 26 publications
4
84
0
Order By: Relevance
“…Only three of these genes have been shown to be hypermethylated in human cancer, CAV1, THBS1, and TNFRSF10B (Li et al, 1999;Cui et al, 2001;Wiechen et al, 2001;Oue et al, 2003;van Noesel et al, 2003). Of these, THBS1 and CAV1 methylation have been linked specifically to breast cancer (Engelman et al, 1999;Li et al, 1999). Conversely, a number of genes that have been shown to be hypermethylated in breast cancer were not scored in this assay including p16, RARb, 14-3-3s, and Cyclin D2 (Foster et al, 1998;Ferguson et al, 2000;Sirchia et al, 2000;Evron et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three of these genes have been shown to be hypermethylated in human cancer, CAV1, THBS1, and TNFRSF10B (Li et al, 1999;Cui et al, 2001;Wiechen et al, 2001;Oue et al, 2003;van Noesel et al, 2003). Of these, THBS1 and CAV1 methylation have been linked specifically to breast cancer (Engelman et al, 1999;Li et al, 1999). Conversely, a number of genes that have been shown to be hypermethylated in breast cancer were not scored in this assay including p16, RARb, 14-3-3s, and Cyclin D2 (Foster et al, 1998;Ferguson et al, 2000;Sirchia et al, 2000;Evron et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CpG-rich regions does not immediately implicate them as regulated by methylation in general or specifically in breast epithelial cells since more than 50% of all human genes may have associated CpG clusters (Murphy and Jirtle, 2001). Only three of these genes have been shown to be hypermethylated in human cancer, CAV1, THBS1, and TNFRSF10B (Li et al, 1999;Cui et al, 2001;Wiechen et al, 2001;Oue et al, 2003;van Noesel et al, 2003). Of these, THBS1 and CAV1 methylation have been linked specifically to breast cancer (Engelman et al, 1999;Li et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The human TSP1 promoter region is equally rich in CpG islands and its hypermethylation goes along with reduced expression of TSP1 in several human malignant tumor cell lines. 115,116 However, VEGF and TSP1 are not the only factors that concern blood flow. Members of the matrix metalloprotease (MMP) family, especially MMP 2 and 9, display pro-angiogenic properties as well.…”
Section: Excitotoxicitymentioning
confidence: 99%
“…Emerging evidence indicates that epigenetic alterations of genes involved in angiogenesis are involved in this switch, and may cause tumors to recruit new blood vessels and sustain their growth (Buysschaert et al, 2008). Glioblastomas, for instance, are typically characterized by excessive blood vessel development and frequently display epigenetic inactivation of the anti-angiogenic thrombospondin-1 (THBS-1) gene (Li et al, 1999). THBS-1 is also suppressed early in breast carcinogenesis by histone modifications (Hinshelwood et al, 2007) and THBS-1 silencing through methylation is observed in a significant portion of primary colorectal adenomas (Rojas et al, 2008).…”
Section: Epigenetic Therapy Targeting Tumor Angiogenesismentioning
confidence: 99%